Pengaruh Pemasaran Eksperiensial Dan Kualitas Layanan Terhadap Kepuasan Konsumen Yang Dimoderasi Oleh Selera (Taste) - Kirana, Domi; Widiastuti , Nur (Syntax Corporation, 2025)
Restaurants are required to improve the quality of service provided to their customers in order to have a positive impact on their restaurants. Consumer satisfaction with fast food restaurants is characterized by high consumer loyalty to the restaurant. Quality service is economically beneficial, simple procedural, and aesthetic to produce consumer satisfaction. Satisfaction evaluates the total quality of service received. The purpose of this study was to determine the effect of experiential marketing and service quality on consumer satisfaction moderated by taste. This study uses a quantitative approach. The population in this study were consumers of Fast Food Restaurants in Yogyakarta City. The sampling technique in this study used simple side random with a sample of 180 samples. Data collection was carried out using a questionnaire. The analysis method used in this study used Partial Least Square (PLS) with the outer model and inner model coefficient tests. The results showed that there was an influence of experiential marketing on consumer satisfaction as evidenced by a significance value of 0.005 <0.05. There was an influence of service quality on consumer satisfaction as evidenced by a significance value of 0.000 <0.05. There is an influence of taste on consumer satisfaction as evidenced by a significance value of 0.049 <0.05. There is no influence of experiential marketing on consumer satisfaction moderated by taste as evidenced by a significance value of 0.280 > 0.05. There is no influence of service quality on consumer satisfaction moderated by taste in fast food restaurants as evidenced by a significance value of 0.909 > 0.05.